PENERAPAN METODE K-MEANS UNTUK PENGELOMPOKKAN KABUPATEN/KOTA DI PROVINSI SUMATERA UTARA BERDASARKAN INDIKATOR INDEKS PEMBANGUNAN MANUSIA - Sibarani, Horainim; Solikhun; Saputra, Widodo; Gunawan, Indra; Nasution, Zulaini Masruro (Institut Teknologi Nasional Malang, 2022)
Human development is a major goal to measure the success of a country. One of the important aspects to measure the level of human development is a society that is superior in terms of quantity and quality, then viewed from the three dimensions of life, namely life opportunities, knowledge, and a decent life. This study discusses the use of the k-means algorithm to group districts/cities in North Sumatra based on the similarity of regional characteristics in terms of four measures of the Human Development Index (IPM). The four measures are Life Expectancy (AHH), Literacy Rate (AMH), Average Length of Schooling (RLS), and Expenditure Per Capita (PPK). Based on the Human Development Index, Life Expectancy, Literacy Rate, Average Years of Schooling and Per Capita Expenditure figures, it is concluded that there are significant differences.